Peran humas DPR RI dalam memperkuat literasi kewarganegaraan masyarakat - Andi Wiratna; Siti Awaliyah; Rista Ayu Mawarti (Universitas Negeri Malang, 2022)
This study aims to discuss the roles, programs, obstacles faced and the efforts made by the Public Relations of the DPR RI in strengthening civic literacy. This study uses a qualitative approach with a descriptive type. Data collection techniques using observation, interviews, and documentation. The data analysis technique uses data collection, data reduction, data presentation and drawing conclusions/verification. The Public Relations of the DPR RI has the role of communicator and facilitator. The program activities carried out are the parliamentary education program, the youth parliament program, the campus parliamentary program and the community visit program. The inhibiting factor in implementing the program is the lack of competent human resources (SDA) in their field, the lack of facilities and infrastructure as well as time allocation. Efforts to overcome obstacles are by conducting natural resource development by participating in training or collaborating with other work units, increasing the number of room capacities used, providing more contemporary innovations, and providing tokens in the form of regulations for the DPR RI, magazines and parliamentary bulletins. so that the information that has been carried out in the activity can be understood again by the community. Kajian ini bertujuan untuk membahas peran, program, kendala yang dihadapi dan upaya yang dilakukan oleh Humas DPR RI dalam memperkuat literasi kewarganegaraan. Kajian ini menggunakan pendekatan kualitatif dengan jenis deskriptif. Teknik pengumpulan data menggunakan observasi, wawancara, dan dokumentasi. Teknik analisis data menggunakan pengumpulan data, reduksi data, penyajian data serta penarikan kesimpulan/verifikasi. Humas DPR RI mempunyai peran komunikator dan fasilitator. Program kegiatan yang dilakukan yakni program edukasi parlemen, program parlemen remaja, program parlemen kampus dan program kunjungan masyarakat. Faktor penghambat dalam pelaksanaan programnya ialah masih minimnya sumber daya manusia (SDA) yang kompeten dibidangnya, minimnya dari segi sarana dan prasarana maupun alokasi waktu. Upaya untuk mengatasi hambatan ialah dengan mengadakan pengembangan SDA dengan cara mengikuti pelatihan ataupun berkolaborasi dengan unit kerja lainnya, peningkatan jumlah kapasitas ruangan yang digunanakan, memberikan inovasi yang lebih kekinian, serta memberikan tanda mata berupa tata tertib DPR RI, majalah dan buletin Parlementeria. agar informasi yang sudah dilaksanakan dalam kegiatan dapat dipahami kembali oleh masyarakat.